Podcast and Padlet and Its' Effectiveness in ELT Class for Pesantren Students - Harisna Hikmah; Ulul Azmi; Wahyu Nugroho (Universitas Cokroaminoto Palopo, 2022)
This study is aimed in improving students’ English productive skills by using podcast and padlet. It apllied quasi-experimental research with pre-test and podcast design. Podcast and Padlet are two free online platform that can be accessed for English language teaching and learning process. The sample of this study consisted of 50 students from MA Assalafiyah who all of them are santri of Pondok Pesantren Assalafiyah. One class was the experimental class and taught by applying podcast and padlet, and the other class was the control class that was taught by using lecturing method. The data were collecting by test of speaking and writing as English productive skills requirement. The t-test was used to analyze the data. The result if the study shown that there were significant differences between students from experimental and control group. The students from experimental group had the higher score on speaking and writing than those from control group.